2009
DOI: 10.1001/archinternmed.2008.574
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid, Pyridoxine, and Cyanocobalamin Combination Treatment and Age-Related Macular Degeneration in Women

Abstract: Context Observational epidemiologic studies indicate a direct association between homocysteine concentration in the blood and risk of age-related macular degeneration (AMD), but randomized trial data to examine the effect of homocysteine-lowering in AMD are lacking. Objective To examine incidence of AMD in a trial of folic acid/vitamin B6/vitamin B12. Design Randomized, double-masked, placebo-controlled trial. Participants 5,442 female health professionals aged 40 years or older with preexisting cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(83 citation statements)
references
References 74 publications
1
81
0
1
Order By: Relevance
“…31 It is well known that an increased homocysteine level increases age-related macular degeneration and risk of stroke; that is why these risks should be considered when evaluating patients who lack folic acid. 32,33 One weakness of our report is that we did not measure the red blood cell folate level, which is evaluated as a better measure of chronic folate deficiency than serum folate level.…”
Section: Retinal Nerve Thinning Secondary To Folic Acid Deficiency 137mentioning
confidence: 97%
“…31 It is well known that an increased homocysteine level increases age-related macular degeneration and risk of stroke; that is why these risks should be considered when evaluating patients who lack folic acid. 32,33 One weakness of our report is that we did not measure the red blood cell folate level, which is evaluated as a better measure of chronic folate deficiency than serum folate level.…”
Section: Retinal Nerve Thinning Secondary To Folic Acid Deficiency 137mentioning
confidence: 97%
“…However, no association was found for folate levels [53]. More recently, a randomized trial of 5442 females revealed a decreased risk of AMD in participants who took daily supplements of folic acid (vitamin B 9 ), pyridoxine (vitamin B 6 ), and cyanocobalamin (vitamin B 12 ) [54]. As with the previously discussed vitamin groups, more research is needed prior to drawing any conclusions regarding the efficacy of using B vitamins to prevent or treat AMD.…”
Section: B Vitaminsmentioning
confidence: 99%
“…In the Women's Antioxidant and Folic Acid Cardiovascular Study (WAFACS), 5,442 female health professionals participated in this randomized, double-masked, placebo controlled trial 132 . Christen et al reported that daily supplementation with folic acid/B 6 /B 12 reduce the risk of AMD in this large cohort of females after an average of 7.3 years of treatment and follow-up.…”
Section: B Vitaminsmentioning
confidence: 99%